The persistence of caste : the Khairlanji murders and India's hidden apartheid - Teltumbde, Anand (Navayana, 2014)
In these Poems on the Genocide in Eelam , edited by Ravikumar, five frontline Tamil poets Cheran, Jayapalan, Yesurasa, Latha, Ravikumar lament the loss of their land, their language and thousands of people. This powerful work demands that we not look away from the genocide in own backyard.